Full-Digital Manni Telescopic Herbst: structural innovation and digital manufacturing - Boggio, Andrea; Cozzani, Mauro; Anelli, Fabrizio; Gastaldi, Giorgio; Manni, Antonio (Frontiers in Dental Medicine, 2025)
IntroductionSkeletal Class II malocclusion, commonly characterized by mandibular retrusion, affects a significant portion of the population and presents challenges in orthodontic correction. The Herbst Appliance has long been used for mandibular advancement, but traditional designs often lead to undesirable dental side effects and mechanical complications. This paper introduces the structural innovation and digital manufacturing of Full Digital Manni Telescopic Herbst (MTH) Appliance, a structurally innovative and digitally manufactured system aimed at enhancing clinical outcomes and reducing treatment failures.Materials and equipmentUtilizing a fully digital workflow, including CAD/CAM design, intraoral scanning, and additive manufacturing, the MTH appliance integrates a full-coverage mandibular splint, digitally designed and precision-engineered maxillary and mandibular components.ResultsThe clinical implementation of the MTH appliance demonstrates excellent fit and high mechanical reliability, reducing lower incisor proclination and offering a proper vertical control. Complications such as debonding or fractures can be significantly reduced and digital reproducibility allows for fast component replacement when needed.Discussion and conclusionThis design improves skeletal correction by enhancing anchorage, minimizing lower incisor proclination, and allowing precise vertical and sagittal control. The digital workflow not only improves fabrication accuracy and patient comfort but also facilitates easy component replacement and reduced chairside time. The MTH appliance sets a new benchmark in Class II treatment, blending digital precision with biomechanical effectiveness.